Studi Komparasi PHBS Warga Sekolah Dasar Di Kota Dan Di Desa Tahun 2015 - Athanasia Budi Astuti; Sunarsih Rahayu; Sri Mulyanti (Interest : Jurnal Ilmu Kesehatan, 2016)
Abstract: PHBS, Resident Of Elementary School. Life Behavior to Clean of Healthy Life (PHBS) will be done to improve the health community. PHBS at school is a group on which was put into practice by the students, teachers and schools community on the basis awareness as learning outcomes so independently to be able to prevent disease, improve their health and play an active role in providing a healthy environment. (Indonesian Ministry of Health, 2007).The aim of the Research is knowing the difference between Elementary School PHBS residents in the City and in the village in 2015. This research is a descriptive comparison. The population of this research is the elementary school in the City and in the village. Sample taken carried out by means purposive sampling. Data Analysis using the tests t independently. The results showed there is a significant difference between elementary school PHBS in the city elementary school with PHBS residents in the village with the p=0,000. Average PHBS respondents elementary school in the city was 35.01 with the standard deviation 6,299, while PHBS elementary school at the village respondents average 30.29 with the standard deviation 7,653. Nurses should work together with the related institution to provide information or health education continually about PHBS in schools.